2012
DOI: 10.1016/j.metabol.2012.05.005
|View full text |Cite
|
Sign up to set email alerts
|

SOD1, but not SOD3, deficiency accelerates diabetic renal injury in C57BL/6-Ins2 diabetic mice

Abstract: Superoxide dismutase (SOD) is a major defender against excessive superoxide generated under hyperglycemia. We have recently reported that renal SOD1 (cytosolic CuZn-SOD) and SOD3 (extracellular CuZn-SOD) isoenzymes are remarkably down-regulated in KK/Ta-Ins2Akita diabetic mice, which exhibit progressive diabetic nephropathy (DN), but not in DN-resistant C57BL/6- Ins2Akita (C57BL/6-Akita) diabetic mice. To determine the role of SOD1 and SOD3 in DN, we generated C57BL/6-Akita diabetic mice with deficiency of SOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 61 publications
0
31
1
Order By: Relevance
“…Whereas one study found that EC-SOD ameliorates ischemic AKI, 15 another study failed to find an effect in a proteinuric diabetic nephropathy model. 17 Although the latter study casts doubt on the importance of EC-SOD, it was unclear whether the result is generalizable to all forms of proteinuric CKD.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Whereas one study found that EC-SOD ameliorates ischemic AKI, 15 another study failed to find an effect in a proteinuric diabetic nephropathy model. 17 Although the latter study casts doubt on the importance of EC-SOD, it was unclear whether the result is generalizable to all forms of proteinuric CKD.…”
Section: Discussionmentioning
confidence: 98%
“…It has previously been shown that intracellular SOD is protective against diabetic nephropathy, 25 although the extracellular isoform was not vital to progression in this disease model. 17 However, the high expression of EC-SOD in the kidney suggests that it plays a key role in maintaining homeostasis. 10 In light of our data, it is now clear that extracellular scavenging of superoxide is necessary in models of proteinuric CKD induced by exposure to ADR, angiotensin II, and albumin overload.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, in mice, the overexpression of SOD has been found to abrogate diabetesinduced renal injuries, most likely due to reduced superoxide-NO interactions [9]. In addition, ablation of the Sod1 gene has been found to result in an acceleration of diabetic renal injuries in both STZ-induced C57BL/6 strains and in C57BL/6-Akita strains [34,35]. Recently, a human genetic study revealed that diabetic risk is correlated with polymorphisms in SOD1 and SOD2 genes [36][37][38].…”
Section: Discussionmentioning
confidence: 99%